Mixed protonic-electronic conducting perovskite oxide as a robust oxygen evolution reaction catalyst - Liu, H.; Yu, J.; Sunarso, J.; Zhou, C.; Liu, B.; Shen, Y.; Zhou, W.; Shao, Zongping (Pergamon, 2018)
Large-scale utilization of hydro, solar, or wind-based electrochemical water splitting relies on the availability of low cost, highly active oxygen evolution reaction (OER) catalyst. Transition metal-containing perovskite oxide is attractive in this regard. The OER on such perovskite oxide in an alkaline solution is nonetheless often limited by proton transfer step. To overcome such limitation, here we apply mixed protonic-electronic conductor BaCo0.8-xFexZr0.1Y0.1O3(x = 0, 0.2, and 0.4) as an OER catalyst. Among these three, BaCo0.8Zr0.1Y0.1O3(BC0.8ZY) in particular shows the lowest OER overpotential, the lowest Tafel slope, the highest OER mass activity, and the highest OER specific activity, which surpass those of Ba0.5Sr0.5Co0.8Fe0.2O3-d(BSCF) benchmark. Using O2-temperature programmed desorption, impedance spectroscopy, and O1s X-ray photoelectron spectroscopy, we attribute such superior OER performance to the highest oxygen desorption capacity, the lowest charge transfer resistance, and the highest hydroxide species content for BC0.8ZY. We also demonstrate that the OER current of BC0.8ZY exhibits a first-reaction order dependence to the solution pH between 12.5 and 14, which confirms its proton transfer rate-determining step.